Does a correlation exist between nasal airway volume and craniofacial morphology: A cone beam computed tomography study - Jeenal V Gupta; P G Makhija; K C Gupta (Wolters Kluwer Medknow Publications, 2016)
Aim: To find the correlation between nasal airway volume and the craniofacial morphology using cone beam computed tomography (CBCT). Materials and Methods: This study consisted of preorthodontic anonymized CBCT scans of 34 healthy adults in the age span of 18-28 years. The volume was calculated using Dolphin 3D R software 11.5 version using semiautomatic segmentation method to calculate nasal volume after determining the nasal airway boundary. The subjects were grouped according to sagittal skeletal relation, craniofacial width, facial index, and facial form. Results: There was statistically significant correlation between nasal volume and craniofacial width (P = 0.009). Conclusion: Nasal volume was correlated only with width of the face and not with width/length ratio of face that could have affected the nasal volume.